Let X and Y be linear subspaces of a Hilbert space $\mathcal{H}$. $\\$

Recall that $\\$

$X + Y$ = {$x+y: x \in X, y \in Y$} $\\$

Show that $\\$

$(X+Y)^\bot$ = $X^\bot\cap Y^\bot$ $\\$

I tried solving the problem as follows;$\\$

Let $z\in(X+Y)^\bot$, if$\;$ $\forall$ $x+y\in(X+Y)$ we have $<z,x+y> = 0$. And if $x+y\neq 0$, this implies $z=0$.Hence $(X+Y)^\bot=z=0$. $\\$

Again from $<z,x+y> = 0$, we have $<z,x+y> = <z,x>+<z,y>=0$. Which implies $z\in X^\bot$ and $z\in Y^\bot$. Thus $X^\bot\cap Y^\bot=z=0$. $\\$

Therefore, $(X+Y)^\bot$ = $X^\bot\cap Y^\bot$. $\\$

I don't know if my working is logically correct. Your comments and hints, would be greatly appreciated. Thanks.

  • $\begingroup$ Your claim that $<z,x+y> = <z,x>+<z,y>=0$ implies $x \in X^{\perp}$ is not correct. You need to show that $<z,x>=0$. Also $<z,x+y>=0$ and $x+y \neq 0$ does not necessarily mean that $z=0$. $\endgroup$
    – Anurag A
    May 15 '19 at 18:06

Let $z \in (X+Y)^{\perp}$. This means $\langle z,u \rangle =0$ for all $u \in X+Y$. In particular, take $u=x+0$, where $x \in X$ and $0 \in Y$ (since $Y$ is a subspace so $0 \in Y$). Thus $\langle z,x \rangle =0$. Consequently $z \in X^{\perp}$.

Now you can proceed similarly to show that $z \in Y^{\perp}$. This would prove that $(X+Y)^{\perp} \subseteq X^{\perp} \cap Y^{\perp}$. You will now have to show the other containment.

  • $\begingroup$ Thanks Anurag. But how do I show the other containment. Hint please. $\endgroup$
    – Prince
    May 15 '19 at 18:19
  • $\begingroup$ To start: consider an element $z$ in $X^\perp\cap Y^\perp$, and try to show $z\perp(X+Y) $. $\endgroup$
    – Berci
    May 15 '19 at 19:28
  • $\begingroup$ @Berci Thanks very much. $\endgroup$
    – Prince
    May 16 '19 at 9:13


$z \in (X + Y)^\bot \tag 1$

we have by definition

$\langle z, x + y \rangle = 0, \; \forall x + y \in X + Y; \tag 2$

so in particular if we take

$y = 0, \tag 3$


$\forall x \in X, \; \langle z, x \rangle = 0 \Longrightarrow z \in X^\bot; \tag 4$

likewise with

$x = 0 \tag 5$

we obtain

$\forall y \in Y, \; \langle z, y \rangle = 0 \Longrightarrow z \in Y^\bot; \tag 6$

combining (4) and (6) yields

$z \in X^\bot \cap Y^\bot, \tag 7$

and thus we have

$(X + Y)^\bot \subset X^\bot \cap Y^\bot. \tag 8$

Going the other way,

$z \in X^\bot \cap Y^\bot \Longrightarrow z \in X^\bot, \; z \in Y^\bot$ $\Longrightarrow \forall (x, y) \in X \times Y, \; \langle z, x \rangle = \langle z, y \rangle = 0, \tag 9$


$\forall x + y \in X + Y, \; \langle z, x + y \rangle = \langle z, x \rangle + \langle z, y \rangle = 0 + 0 = 0, \tag{10}$


$X^\bot \cap Y^\bot \subset (X + Y)^\bot. \tag{11}$

Now by virtue of (8) and (11) we conclude that

$(X + Y)^\bot = X^\bot \cap Y^\bot. \tag{12}$


  • 1
    $\begingroup$ Thanks alot. You've made all simple and clear. Thanks. $\endgroup$
    – Prince
    May 16 '19 at 9:19
  • $\begingroup$ You are most welcome, sir. Cheers! $\endgroup$ May 16 '19 at 16:10

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.